2018
DOI: 10.1186/s40942-018-0145-8
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes of epiretinal membrane peeling in patients with foveal herniation

Abstract: BackgroundTo evaluate the surgical outcomes of vitrectomy in patients with foveal herniation associated with epiretinal membrane (ERM).MethodsThis was a retrospective case series. The patients who had a foveal herniation associated with ERM, underwent vitrectomy, and had a minimum follow-up period of 12 months were included. The visual and anatomical outcomes were assessed during the first 12 months of follow-up and at the last follow-up visit. The main outcome measure was the reorganization pattern of foveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Similar to other reports, a visual gain was found in our study with an average of three lines after the macular surgery. Restoration of the foveal contour was achieved in 35.5%, which was comparable to previous studies reporting between 32.2% and 45.4% of successful restoration [ 12 , 13 ]. In our population, eyes having intraocular gas (16.2%) had higher chance of restoration of the foveal contour.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar to other reports, a visual gain was found in our study with an average of three lines after the macular surgery. Restoration of the foveal contour was achieved in 35.5%, which was comparable to previous studies reporting between 32.2% and 45.4% of successful restoration [ 12 , 13 ]. In our population, eyes having intraocular gas (16.2%) had higher chance of restoration of the foveal contour.…”
Section: Discussionsupporting
confidence: 86%
“…In our population, eyes having intraocular gas (16.2%) had higher chance of restoration of the foveal contour. Intraocular gas tamponade was used more frequently in other studies (54.5–86%) than in our study [ 12 , 13 ]. No correlation between the improvement of the vision and the use of tamponade or restoration of the foveal contour was found.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…8–10 Previous studies have suggested that excessive centripetal forces from the ERM formed on the surface may create sufficient traction to pull the inner retinal layers into the vitreous through the central operculum leading to the herniation. 2,6,7 However, we believe that the increased volume of retina within the sub-ERM compartment after the ERM traction-related inner retinal layer thickening causes increased tissue pressure and retinal herniation through a central aperture within the ERM. Oellers and Eliott 2 suggest that retinal edema secondary to ERM traction may also result in the foveal tissue protrusion.…”
Section: Discussionmentioning
confidence: 99%
“…5 Francis et al 4 reported a series of six patients with foveal herniation who had improved visual and anatomical outcomes after surgical ERM peeling. Ozkaya et al 6 described a retrospective case series of outcomes of ERM peeling in 11 patients with foveal herniation. Similar to our study, their findings included complete restoration of the foveal contour in approximately half the patients with an improvement in visual acuity postoperatively.…”
Section: Discussionmentioning
confidence: 99%